Das Torgau-Tabu : Wehrmachtstrafsystem, NKWD-Speziallager, DDR-Strafvollzug - Haase, Norbert 1960- Hrsg; Dörner, Bernward 1956- (Forum-Verl, 1993)
Wehrmachtstrafsystem, NKWD-Speziallager, DDR- Straflvorllzug